Durability and strength degradation of xanthan gum based biopolymer treated soil subjected to severe weathering cycles - Lee, Minhyeong; Kwon, Yeong Man; Park, Dong Yeup; Chang, Ilhan; Cho, Gye Chun (Scientific Reports, 2022)
Biopolymer-based soil treatments have shown effectiveness in soil improvement, with successful field-scale implementation. In this study, we explored the effect of cyclic wetting–drying (W–D) and freezing–thawing (F–T) on the strength durability of biopolymer-treated soils. The results indicate that cyclic W–D and F–T gradually degrade soil strength owing to water adsorption and local biopolymer dilution. Poorly graded sand was highly vulnerable to these weathering effects; however, this problem was mitigated when the soil contained a fines content of 15–25%. These biopolymer-treated soils effectively resisted numerous cycles of both W–D and F–T, indicating that biopolymer-treated soils are suitable for earthen slope reinforcement.
Keywords: Biopolymers; Polysaccharides, Bacterial; Soil; Soil Pollutants